2013
DOI: 10.6002/ect.2013.0018
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Might Be a Favorable Antiobesity Drug For New Onset Diabetes After a Renal Transplant

Abstract: Objectives: The aim of this study was to evaluate the effectiveness of sitagliptin, alone or in combination with metformin, in kidney transplant patients with newly diagnosed new-onset diabetes mellitus after transplant who had inadequate glycemic control, compared with a group of patients receiving insulin glargine with special emphasis on weight gain. Materials and Methods: Newly diagnosed renal transplant patients with new-onset diabetes mellitus after a transplant was defined by a blood glucose ≥ 11.1 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…25 The combination of metformin and sitagliptin led to greater weight reductions than with metformin and insulin glargine (−0.4 vs +0.8 kg; P < 0.05) at 12 weeks. 30 Reductions in BMI were observed after 12 months of treatment (−0.8 kg/m 2 ; P < 0.05). 28 As for safety, DPP-4 inhibitors are well tolerated, with mild GI AEs.…”
Section: Dipeptidyl Peptidase-4 Inhibitorsmentioning
confidence: 90%
“…25 The combination of metformin and sitagliptin led to greater weight reductions than with metformin and insulin glargine (−0.4 vs +0.8 kg; P < 0.05) at 12 weeks. 30 Reductions in BMI were observed after 12 months of treatment (−0.8 kg/m 2 ; P < 0.05). 28 As for safety, DPP-4 inhibitors are well tolerated, with mild GI AEs.…”
Section: Dipeptidyl Peptidase-4 Inhibitorsmentioning
confidence: 90%
“…1 Even though insulin has been considered the treatment of choice in transplanted patients first presenting with hyperglycemia, 12 oral antidiabetic drugs are used frequently in NODAT. In 1 study, there was no difference in glycemic control when adding an oral agent such as sitagliptin as compared with insulin glargine, 13 and another recent randomized study showed that DPP-4 inhibition in kidney transplant recipients with overt NODAT was safe and efficient. 14 In this retrospective cohort study in kidney-transplanted patients with NODAT, we aim to better define the association between fasting plasma glucose/HbA1C values and patient/graft survival and cardiovascular outcome and to examine glucose control of different treatment modalities in NODAT.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of PTDM has been reported different in the literature. The majority of the scholars have opined that the potential low insulin secretion of PTDM patients are aggravated by the immunosuppressor and their B cells are susceptible to anti-rejection medicines [20][21][22]. Research has also indicated that the state of insulin resistance is present in patients with terminal kidneydiseases; application of hormones further lowers the sensitivity of the peripheral insulin following transplantation; in addition, the insulin secretion defect caused by calcineurin inhibitor also accelerates the progression of PTDM [23][24].…”
Section: Discussionmentioning
confidence: 99%